2019
DOI: 10.1016/j.heliyon.2019.e01540
|View full text |Cite|
|
Sign up to set email alerts
|

Co-innovation processes in the music business

Abstract: This study aims to develop a framework grounded in theoretical and empirical findings regarding the ways in which co-innovation processes are carried out in the context of the Indonesian music industry. This study uses a qualitative case research method via interviews. Through literature reviews, four key concepts are proposed as the basis of rival analyses to the empirical findings. From the data collection and analysis, this study establishes that co-innovation processes in the music business constitute four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
(61 reference statements)
1
22
0
Order By: Relevance
“…Co-innovation is defined as the process that allows the participation of the different stakeholders in the company (clients, suppliers, external collaborators, partner organizations, and the general public), through collaborative work networks, in the creation and development of new products and services, as well as processes or even business models; that is to say, co-innovation achieves value creation for the company through the active participation of external actors (Saragih et al., 2019; Bugshan, 2015; Lee et al., 2012; Romero and Molina, 2011).…”
Section: Theorymentioning
confidence: 99%
“…Co-innovation is defined as the process that allows the participation of the different stakeholders in the company (clients, suppliers, external collaborators, partner organizations, and the general public), through collaborative work networks, in the creation and development of new products and services, as well as processes or even business models; that is to say, co-innovation achieves value creation for the company through the active participation of external actors (Saragih et al., 2019; Bugshan, 2015; Lee et al., 2012; Romero and Molina, 2011).…”
Section: Theorymentioning
confidence: 99%
“…As a continuation of the above, Saragih et al (2019) adjusted and revised their initial conceptualisations by using the abductive paradigm and case research methods to compare the empirical findings with the initial conceptual framework (Perry and Jensen, 2001;Kovács and Spens, 2005;Blaikie, 2007). Their study concluded that the co-innovation process comprises four stages: co-discovery, co-creation, co-delivery and co-capture (Table II).…”
Section: Co-innovation Process In the Music Businessmentioning
confidence: 99%
“…In the music business, co-discovery constitutes several key concepts, i.e. establishing shared values, initiating governance and leadership, justifying benefits, gaining trust and building engagement amongst the contributing actors (Saragih et al, 2019). This stage focuses on the philosophical stance of why the platform for creativity and innovation is initiated.…”
Section: Co-innovation Process In the Music Businessmentioning
confidence: 99%
See 2 more Smart Citations